RRMdb—an evolutionary-oriented database of RNA recognition motif sequences. (16th January 2019) - Nowacka, Martyna; Boccaletto, Pietro; Jankowska, Elzbieta; Jarzynka, Tomasz; Bujnicki, Janusz M; Dunin-Horkawicz, Stanislaw
Abstract: RNA-recognition motif (RRM) is an RNA-interacting protein domain that plays an important role in the processes of RNA metabolism such as the splicing, editing, export, degradation, and regulation of translation. Here, we present the RNA-recognition motif database (RRMdb), which affords rapid identification and annotation of RRM domains in a given protein sequence. The RRMdb database is compiled from ~57 000 collected representative RRM domain sequences, classified into 415 families. Whenever possible, the families are associated with the available literature and structural data. Moreover, the RRM families are organized into a network of sequence similarities that allows for the assessment of the evolutionary relationships between them.